Tax Planning, Regulatory Capital Planning, and Financial Reporting Strategy for Commercial Banks - Scholes, Myron S.; Wilson, G. Peter; Wolfson, Mark A. (Review of Financial Studies, 1990)
We test whether banks’ investment and financing policies can be explained by tax status. We document changes in bank holdings of municipal bonds in response to changes in tax rules relating to deductibility of interest expense. We also document an association between banks’ marginal tax rates and their investment and financing decisions, which is consistent with the existence of tax clienteles. However, banks do not sort themselves perfectly into investment and financing clienteles because of adjustment costs. We posit specific types of transaction-cost impediments to tax planning, and document that banks apparently trade off these costs against tax-planning benefits.